The Cambridge Handbook of Child Language - Bavin, Edith L.; Naigles, Letitia R. (Cambridge : Cambridge University Press, 2015)
The most authoritative resource for students and researchers, The Cambridge Handbook of Child Language has been thoroughly updated and extended. Enhancements include new chapters on the acquisition of words, processing deficits in children with specific language impairments, and language in children with Williams syndrome, new authors for the bilingualism and autism chapters, a refocused discourse chapter on written narratives, and a new section on reading and reading disorders, cementing the handbook's position as the best study of the subject available. In a wide-ranging survey, language development is traced from prelinguistic infancy to adolescence in typical and atypical contexts; the material is intuitively grouped into six thematic sections, enabling readers to easily find specific in-depth information. With topics as varied as statistical learning, bilingualism, and the neurobiology of reading disorders, this multidisciplinary Handbook is an essential reference for students and researchers in linguistics, psychology, cognitive science, speech pathology, education and anthropology.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).